2011
DOI: 10.1053/j.gastro.2011.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Spermine Oxidase Mediates the Gastric Cancer Risk Associated With Helicobacter pylori CagA

Abstract: BACKGROUND & AIMS Helicobacter pylori-induced gastric carcinogenesis has been linked to the microbial oncoprotein CagA. Spermine oxidase (SMO) metabolizes the polyamine spermine into spermidine and generates H2O2 that causes apoptosis and DNA damage. We determined if pathogenic effects of CagA are attributable to SMO. METHODS Levels of SMO, apoptosis, and DNA damage (8-oxoguanosine) were measured in gastric epithelial cell lines infected with cagA+ or cagA− H. pylori strains, or transfected with a CagA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
182
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 175 publications
(190 citation statements)
references
References 41 publications
6
182
0
2
Order By: Relevance
“…The most abundant PG produced by COX-2 in gastric cancer is PGE 2 (22). PGE 2 binds to four subtypes of receptors (EP 1 -EP 4 ) and promotes tumor growth by stimulating cell proliferation, promoting angiogenesis, inhibiting apoptosis, inducing invasion, and suppressing immune activation (25).…”
Section: Cyclooxygenase-2; Egfr; Helicobacter Pylorimentioning
confidence: 99%
“…The most abundant PG produced by COX-2 in gastric cancer is PGE 2 (22). PGE 2 binds to four subtypes of receptors (EP 1 -EP 4 ) and promotes tumor growth by stimulating cell proliferation, promoting angiogenesis, inhibiting apoptosis, inducing invasion, and suppressing immune activation (25).…”
Section: Cyclooxygenase-2; Egfr; Helicobacter Pylorimentioning
confidence: 99%
“…These data were confirmed by flow cytometry of isolated gastric epithelial cells from human tissues. 24 We also showed that in C57BL/6 mice chronically infected with H. pylori PMSS1, a strain that maintains the ability to translocate CagA into gastric epithelial cells after in vivo passage, 32 there were increased levels of SMO protein in gastric epithelial cells when assessed by flow cytometry. 24 In contrast, mice infected with a PMSS1 cagE -mutant exhibited no significant increase in SMO expression in gastric epithelial cells.…”
mentioning
confidence: 67%
“…31 We found higher levels of CagA protein in ImSt cells co-cultured with 7.13, compared with its non-carcinogenic parental strain B128. 24 Co-culture of 7.13 with ImSt cells resulted in higher levels of SMO mRNA expression compared with coculture with B128, and the 7.13 cagA -mutant failed to increase SMO mRNA levels. Similarly, when assessed by western blotting or flow cytometry, H. pylori strain 7.13 significantly upregulated SMO protein levels, which were induced to a lesser degree with B128, and the 7.13 cagA -strain did not increase SMO protein expression.…”
mentioning
confidence: 89%
See 2 more Smart Citations